2002
DOI: 10.1038/sj.cgt.7700421
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfection by quantitatively reconstituted Sendai envelope proteins into liposomes

Abstract: Fusogenic liposomes ( virosomes ) consisting of Sendai virus envelope proteins have been utilized for in vitro and in vivo genetic modification of animal cells. In this study, the virosomes containing DNA were prepared by quantitative reconstitution of Sendai envelope proteins, fusion protein and hemagglutinin -neuramindase in liposomal vesicles. The Sendai virosomes more efficiently transferred genes into cultured 293 transformed kidney cells than 1,2 -dioleoyl -3 -( trimethylammonium ) propane -based cationi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Recently we also reported that negatively-charged PS that contained Sendai virosomes efficiently transfer genes into cultured cells (Kim and Park, 2002). However, among the electron negatively-charged virosomes, the ASVE-and PSvirosomes were relatively efficient in gene transfer while the PA-virosomes were not (Fig.…”
Section: In Vitro Gene Transfer Mediated By F/hn-virosomes Of Varied mentioning
confidence: 98%
See 2 more Smart Citations
“…Recently we also reported that negatively-charged PS that contained Sendai virosomes efficiently transfer genes into cultured cells (Kim and Park, 2002). However, among the electron negatively-charged virosomes, the ASVE-and PSvirosomes were relatively efficient in gene transfer while the PA-virosomes were not (Fig.…”
Section: In Vitro Gene Transfer Mediated By F/hn-virosomes Of Varied mentioning
confidence: 98%
“…The fusogenic proteins that were reconstituted into the virosomes were another major factor that governed transfection efficiency. In this study, the F/HN-proteins were reconstituted at a 1 : 100 weight ratio of protein to lipid, the ratio at which in vitro gene transfection has been found to be the most efficient (Kim and Park, 2002).…”
Section: In Vitro Gene Transfer Mediated By F/hn-virosomes Of Varied mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover lipid vesicles also do not release the incorporated molecule instantaneously so they can act as local depot for sustained release of drug or immunogen. Some commonly employed vesicular carriers that facilitate permeation includes liposomes [5,63], niosomes [5,63,64], transfersomes [63,65], virosomes [66] Reconstituted Sandai Virus Envelop (RSVE) [69][70] etc. The driven forces, which are involved in selective transfer of lipid vesicles through intact skin, are osmotic gradient and hydration force generally.…”
Section: Transfersomes Niosomes and Liposomesmentioning
confidence: 99%
“…15 We have developed a novel Sendai F/HN virosome system for in vivo gene transfection. The Sendai virosome formulations were optimized for in vitro and in vivo transfection, especially systemic gene delivery.…”
Section: Introductionmentioning
confidence: 99%